Inovasi Berkelanjutan dalam Agribisnis: Kajian Literatur tentang Model Kewirausahaan Hijau - Sasongko, Lutfi Aris; Ni'mah, Lu'lu'a Ulyn (Universitas Wahid Hasyim, 2025)
Sustainable innovation in the agribusiness sector plays a crucial role in enhancing productivity, improving energy efficiency, and ensuring environmental sustainability. This article provides an in-depth discussion on the green entrepreneurship model, the factors that support or hinder the implementation of green innovations, and the role of digital technology in accelerating the transformation of the agribusiness sector. The research method employed in this study is a systematic literature review, in which data were collected and analyzed from various studies published in national and international journals over the past fifteen years. The findings indicate that green innovations, such as the adoption of the Internet of Things (IoT), Artificial Intelligence (AI), blockchain, and the circular economy concept, significantly contribute to improving production efficiency while reducing negative environmental impacts. However, the implementation of these innovations faces several challenges, including high initial costs, a lack of supportive regulations, and resistance from farmers toward adopting new technologies. Support from the government, academia, the private sector, and farming communities is a key factor in promoting the adoption of green innovations in the agribusiness sector. This article recommends the need for more pro-green innovation policies, increased access to sustainable funding, and strengthened cross-stakeholder collaboration to establish a more resilient green agribusiness ecosystem. Through an integrated approach, green innovation is expected to serve as a tangible solution for developing a robust, efficient, and environmentally friendly agribusiness sector in the future. Keywords: Green Entrepreneurship, Agribusiness, Digital Technology, Circular Economy, Sustainability